Defining wet season water quality target concentrations for ecosystem conservation using empirical light attenuation models: A case study in the Great Barrier Reef (Australia). (1st May 2018) - Petus, Caroline; Devlin, Michelle; Teixera da Silva, Eduardo; Lewis, Stephen; Waterhouse, Jane; Wenger, Amelia; Bainbridge, Zoe; Tracey, Dieter
Abstract: Optically active water quality components (OAC) transported by flood plumes to nearshore marine environments affect light levels. The definition of minimum OAC concentrations that must be maintained to sustain sufficient light levels for conservation of light-dependant coastal ecosystems exposed to flood waters is necessary to guide management actions in adjacent catchments. In this study, a framework for defining OAC target concentrations using empirical light attenuation models is proposed and applied to the Wet Tropics region of the Great Barrier Reef (GBR) (Queensland, Australia). This framework comprises several steps: (i) light attenuation (Kd(PAR)) profiles and OAC measurements, including coloured dissolved organic matter (CDOM), chlorophyll-a (Chl-a) and suspended particulate matter (SPM) concentrations collected in flood waters; (ii) empirical light attenuation models used to define the contribution of CDOM, Chl-a and SPM to the light attenuation, and; (iii) translation of empirical models into manageable OAC target concentrations specific for wet season conditions. Results showed that (i) Kd(PAR) variability in the Wet Tropics flood waters is driven primarily by SPM and CDOM, with a lower contribution from Chl-a (r2 = 0.5, p < 0.01), (ii) the relative contributions of each OAC varies across the different water bodies existing along flood waters and strongest Kd(PAR) predictions were achieved when the in-situ data were clustered into water bodies with similar satellite-derived colour characteristics ('brownish flood waters', r2 = 0.8, p < 0.01, 'greenish flood waters', r2 = 0.5, p < 0.01), and (iii) that Kd(PAR) simulations are sensitive to the angular distribution of the light field in the clearest flood water bodies. Empirical models developed were used to translate regional light guidelines (established for the GBR) into manageable OAC target concentrations. Preliminary results suggested that a 90th percentile SPM concentration of 11.4 mg L −1 should be maintained during the wet season to sustain favourable light levels for Wet Tropics coral reefs and seagrass ecosystems exposed to 'brownish' flood waters. Additional data will be collected to validate the light attenuation models and the wet season target concentration which in future will be incorporated into wider catchment modelling efforts to improve coastal water quality in the Wet Tropics and the GBR. Highlights: This study focuses on the Great Barrier Reef Marine Park, Australia. Light attenuation and optical active components data were sampled in river plumes. Relationship between light and optical active components was empirically modelled. Models helped translating light guidelines into water quality target concentrations. Targets will help maintaining sufficient light levels for ecosystems conservation.